The Poetics of Anti-Colonialism in the Arabic Qaṣīdah - Kadhim, Hussein (Brill, 2024)
Representing the most sustained investigation of the aesthetics of Anti-Colonialism in modern Arabic poetry, this book chronicles the evolution of a distinct poetics that sought to maintain the integrity of the qaṣīdah without circumventing its historical moment. It painstakingly analyses a selection of odes by four leading twentieth-century poets, Aḥmad Shawqī, Maʿrūf al-Ruṣāfī, Badr Shākir al-Sayyāb and ʿAbd al-Wahhāb al-Bayātī. It will be of particular interest to scholars and students of Arabic literature, Islamic and Middle Eastern studies, Postcolonial studies, Comparative literature, and Cultural studies.